Manajemen Kurikulum dan Sistem Penilaian Pendidikan : Studi Kasus di SMP Negeri 19 Kota Tangerang Selatan - Jamilah Muryati; Munandar, Aris; Naufal Hilmizen; Sulastini, Rita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the implementation of curriculum management and educational assessment. This research uses qualitative methods with data collection techniques using interviews, document review, observation. The research location is at SMPN 19 South Tangerang City. In curriculum management, planning, organizing, implementing, monitoring and evaluating as well as the assessment system has been implemented in accordance with applicable National Curriculum standards, this is supported by adequate facilities and infrastructure with the availability of internet, electricity and computers as well as professional teachers and teaching staff. . To process grades using both the independent curriculum and the 2013 curriculum by utilizing technology to simplify the assessment process, technology-based evaluation tools, and data analysis of assessment results until the final results are contained in e-reports.